Gambling behavior in alcohol-serving and non-alcohol-serving-venues: a study of electronic gaming machine players using account records. (4th May 2017) - Leino, Tony; Molde, Helge; Griffiths, Mark D.; Mentzoni, Rune A.; Sagoe, Dominic; Pallesen, Ståle
Abstract: Aim: Contextual factors, such as venue characteristics appear to influence gambling behavior. However, few studies have compared the relationship between gambling behavior in alcohol-serving venues (ASVs) and non-alcohol serving venues (NASVs). The aim of the study was to examine individual gambling behavior in ASVs and NASVs. Method: A repeated-measures design was used to examine individual gambling behavior in ASVs and NASVs covering a month. The sample comprised 1452 observations of 726 individuals (25.2% female). A quantile regression model was conducted to examine individual differences in gambling behavior (number of days, sessions, bets made, stake, time spent, money lost, and average bet size) across ASVs and NASVs. Analyses were broken down by gambler category (those that reached legal mandatory spending limits and those that did not) as well as on time frame (overall gambling behavior and average in-session gambling behavior). Results: Individuals gambled regularly in NASVs and occasionally in ASVs. Compared to NASVs, in-session gambling behavior was more variable in ASVs. In-session analysis showed that non-limit reaching gamblers staked less money in ASVs than in NASVs but lost more money in ASVs than in NASVs. Limit reaching gamblers showed no differences in gambling behavior across venues. Conclusions: The findings show that in-session gambling behavior is more variable in ASVs compared to NASVs regardless of gambling category. Non-limit reaching gamblers may be more sensitive to contextual factors than limit reaching gamblers and appear to be more willing to take more risk in ASVs compared to NASVs. The contextual implications are discussed.